2018
DOI: 10.1007/s00586-018-5633-x
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-only versus combined anterior/posterior fusion in Scheuermann disease: a large retrospective study

Abstract: Surgery for Scheuermann's kyphosis gives good and stable functional and radiological results. Given the fact that the two surgical strategies give the same results, it appears that the anterior/posterior fusion technique to treat Scheuermann's kyphosis should be reserved for major deformations. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…As presented in Figure 1 , after database search, there were 95 relevant papers included in the first-round literature selection. After study selection, 13 unique studies [ 4 , 6 , 10 , 14 22 ] including 586 patients (AP: 300; PO: 286) were identified and included for this meta-analysis. Overall, 6 AP cohorts and 10 PO cohorts were pooled regarding the correction degrees of kyphosis in the analysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As presented in Figure 1 , after database search, there were 95 relevant papers included in the first-round literature selection. After study selection, 13 unique studies [ 4 , 6 , 10 , 14 22 ] including 586 patients (AP: 300; PO: 286) were identified and included for this meta-analysis. Overall, 6 AP cohorts and 10 PO cohorts were pooled regarding the correction degrees of kyphosis in the analysis, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2 , six studies [ 6 , 10 , 16 , 19 , 21 , 22 ] reported the correction effect by AP and were pooled into the meta-analysis. As a result, pooled correction degrees in AP cohorts were 33.31 (95% CI: 27.48–39.15; I 2 = 86%, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations